2012
DOI: 10.1089/ars.2012.4553
|View full text |Cite
|
Sign up to set email alerts
|

Glutathione Efflux and Cell Death

Abstract: Significance: Glutathione (GSH) depletion is a central signaling event that regulates the activation of cell death pathways. GSH depletion is often taken as a marker of oxidative stress and thus, as a consequence of its antioxidant properties scavenging reactive species of both oxygen and nitrogen (ROS/RNS). Recent Advances: There is increasing evidence demonstrating that GSH loss is an active phenomenon regulating the redox signaling events modulating cell death activation and progression. Critical Issues: In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
138
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 200 publications
(142 citation statements)
references
References 255 publications
(141 reference statements)
2
138
0
2
Order By: Relevance
“…However, this denitrosylation system is dependent on cellular levels of reduced glutathione, which initially acts as a NO sink. Under physiological conditions, glutathione reductases reduce GSSG to GSH [93]. Under pathological conditions, ROS and RNS may cause GSH depletion by its oxidation to GSSG [94,95].…”
Section: Depletion Of Glutathione and Subsequent Loss Of Denitrosylationmentioning
confidence: 99%
“…However, this denitrosylation system is dependent on cellular levels of reduced glutathione, which initially acts as a NO sink. Under physiological conditions, glutathione reductases reduce GSSG to GSH [93]. Under pathological conditions, ROS and RNS may cause GSH depletion by its oxidation to GSSG [94,95].…”
Section: Depletion Of Glutathione and Subsequent Loss Of Denitrosylationmentioning
confidence: 99%
“…It has been shown that the decrease of GSH content is a common feature in apoptotic cell death (38). Previous studies reported that plumbagin regulates the cellular redox state by modulation of GSH (36,39).…”
Section: Gsh Depletion By Plumbagin Increases the Production Of Rosmentioning
confidence: 99%
“…Under certain circumstances, such as in the onset of apoptosis, glutathione could efflux from the cells (Oda et al, 1999), which lowers the reducing capability of the cells and can consequently result in oxidative stress without interference of ROS generation. Therefore, GSH depletion is often taken as a marker of oxidative stress (Franco and Cidlowski, 2012). Oxidative stress causes profound alterations of various biological structures, including cellular membranes, lipids, proteins and nucleic acids, and it is involved in numerous malignancies.…”
Section: Discussionmentioning
confidence: 99%